Statistical abstract of the United States. (Washington : U.S. Dept. of Commerce, Bureau of the Census, 1994)
"The standard summary of statistics on the social, political, and economic organization of the United States.
"National Data Book and Guide to Sources."
Chiefly tables.
1st-67th no.; 68th- ed.
7th and 8th numbers issued as one volume.
66th number covers 1944-45.
1st-25th no., 1878-1902, issued by the Bureau of Statistics (Treasury Dept.); 26th-34th no., 1903-11, issued by the Bureau of Statistics (Dept. of Commerce and Labor); 35th no., 1912,issued by the Bureau of Foreign and Domestic Commerce (Dept. of Commerce and Labor); 36th-59th no., 1913-37, issued by the Bureau of Foreign and Domestic Commerce (Dept. of Commerce); 60th- no., 1938- , issued by the Bureau of the Census.
Keywords: United States -- Statistics